2020
DOI: 10.3389/fneur.2020.573642
|View full text |Cite
|
Sign up to set email alerts
|

Hand Focused Upper Extremity Rehabilitation in the Subacute Phase Post-stroke Using Interactive Virtual Environments

Abstract: Introduction: Innovative motor therapies have attempted to reduce upper extremity impairment after stroke but have not made substantial improvement as over 50% of people post-stroke continue to have sensorimotor deficits affecting their self-care and participation in daily activities. Intervention studies have focused on the role of increased dosing, however recent studies have indicated that timing of rehabilitation interventions may be as important as dosing and importantly, that dosing and timing interact i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Since it has been suggested that a higher dose of training volume is preferable, with more than 15 h of total intervention time (Laver et al, 2017), future studies are needed to determine if the dose of VR-therapy does have a significant effect on motor rehabilitation outcomes and if so, which dosage has to be applied when implementing VR in therapy. Future studies will also help specify the effects of timing of VR interventions on functional outcomes and thus, may help determine the optimal timing during which VR interventions can lead to significant improvements in stroke rehabilitation (Merians et al, 2020).…”
Section: Perspectives On the Future Of Virtual Reality In Clinical Settings And Researchmentioning
confidence: 99%
“…Since it has been suggested that a higher dose of training volume is preferable, with more than 15 h of total intervention time (Laver et al, 2017), future studies are needed to determine if the dose of VR-therapy does have a significant effect on motor rehabilitation outcomes and if so, which dosage has to be applied when implementing VR in therapy. Future studies will also help specify the effects of timing of VR interventions on functional outcomes and thus, may help determine the optimal timing during which VR interventions can lead to significant improvements in stroke rehabilitation (Merians et al, 2020).…”
Section: Perspectives On the Future Of Virtual Reality In Clinical Settings And Researchmentioning
confidence: 99%
“…This said, the two studies from this metanalysis that focused on the acute and first few weeks of the recovery stage both found non-significant trends favoring VR based interventions ( 23 , 39 ). Our group has initiated a large scale clinicial trial addressing this topic as well as comparisons with a dose–matched program of traditional rehabilitation and a delayed onset program of virtual rehabilitation ( 40 ).…”
Section: Rehabilitation Early After Strokementioning
confidence: 99%
“…Two groups using slightly different methods found no training related changes in map area ( 45 , 46 ). These differing outcomes identified across our clinical, kinematic and neurophysiological studies examining the rehabilitation of persons with chronic stroke and those of our pilot studies of earlier virtual rehabilitation, have led us to initiate a larger study, adding a fourth group of subjects that perform an additional 10 h of traditional rehabilitation in an attempt to control for the timing of hand focused intervention, the dose of rehabilitation intervention, and the additive value of VR virtual reality-based rehabilitation ( 40 ).…”
Section: Impact Of Vr Training On Cortical Excitatabilitymentioning
confidence: 99%
See 1 more Smart Citation